(untitled) (Lafia Journal of Scientific and Industrial Research, 2026)
The global shift to sustainable materials has intensified research on agricultural waste materials like rice husk as they can produce high-purity silica. The process of silica extraction through traditional hot leaching methods requires excessive energy and creates environmental pollution. The research project aims to investigate how leaching processes affect material composition. The researchers assessed silica through multiple methods which included Scanning Electron microscopy-energy dispersive spectroscopy (SEM-EDS) X-ray fluorescence (XRF) X-ray Diffraction (XRD) and Thermogravimetric Analysis-Differential Thermal Analysis (TGA-DTA). The treated silica reached 97% purity while maintaining a dense structure and minimal impurities and it demonstrated thermal stability that extended beyond 600 °C. The H₂SO₄-treated silica achieved 96% purity but its thermal stability decreased to 680 °C while HNO₃-treated silica with 95% purity exhibited carbon content of 3.05% and reduced thermal stability because of incomplete organic matter removal. XRD confirmed that all the samples exist as amorphous materials. The SEM-EDS analysis showed that HCL treatment resulted in the most effective impurity reduction because this sample showed the best compact morphology. The (TGA-DTA) analysis demonstrated weight-loss at various stages which occurred during moisture loss and organic matter decomposition while the material maintained stable thermal properties at high temperatures.